2000
DOI: 10.3354/meps200059
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fluxes, denitrification and the role of microphytobenthos in microtidal shallow-water sediments:an annual study

Abstract: The annual cycle of oxygen and nitrogen flux, denitrification and microphytobenthic variables (primary production, biomass, composition and calculated N demand) were studied for 2 shallow-water microtidal sediment sites in NE Kattegat, 1 sandy and 1 silty, by incubating undisturbed sediment in the laboratory in light and darkness. Both sites (2 stations within each) were characterised by low concentrations of inorganic nitrogen (IN), in the overlying water during summer (NO3 generally < l pM), with winter conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(147 citation statements)
references
References 34 publications
8
135
1
Order By: Relevance
“…In general this is expected since denitrification in marine sediments is a temperature dependent process (Rysgaard et al 2004). On the other hand, our finding is in contrast with other studies from temperate estuaries and coastal systems, where lower denitrification rates were observed in summer during limiting NO 3 -and O 2 conditions Cabrita and Brotas 2000;Sundbäck et al 2000). At B1, H2 and H4, however, O 2 was never limiting and NO 3 -for denitrifiers was mainly generated through nitrification.…”
Section: Discussioncontrasting
confidence: 56%
“…In general this is expected since denitrification in marine sediments is a temperature dependent process (Rysgaard et al 2004). On the other hand, our finding is in contrast with other studies from temperate estuaries and coastal systems, where lower denitrification rates were observed in summer during limiting NO 3 -and O 2 conditions Cabrita and Brotas 2000;Sundbäck et al 2000). At B1, H2 and H4, however, O 2 was never limiting and NO 3 -for denitrifiers was mainly generated through nitrification.…”
Section: Discussioncontrasting
confidence: 56%
“…Microphytobenthos take up nutrients not only from the water column but also from pore water (Henriksen et al, 1980;Sundbäck et al, 1991;Cahoon and Cooke, 1992;Cahoon, 1999;Sundbäck et al, 2000;Srithongouthai et al, 2003). In this study, the mean standing stock of microphytobenthos inhabiting surface sediment (5 mm thick) on tidal flats was 100 times higher than that of phytoplankton (1 m depth; see section 3.3).…”
Section: Nutrient Budgetmentioning
confidence: 73%
“…Previously, in situ measurements using light and dark chambers on tidal flats have shown that the efflux of NH 4 -N from the sediment depends on the photosynthetic activity of microphytobenthos (Sundbäck et al, 1991;Sundbäck et al, 2000;Sandwell et al, 2009). In the continuous survey of this study, the factor loading of NH 4 -N was significantly negative but lower than the other nutrients, it seemed to reflect the effect of both physical variables (i.e., tidal height) and photosynthetic activity (i.e., solar radiation) ( Table 1, Fig.…”
Section: Nutrient Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…GPP was expressed in carbon units applying photosynthetic quotient O 2 :C=1.2 (Bartoli et al, 2012) in order to estimate theoretical N, P, and Si requirements by microphytobenthos (Table 6). Theoretical nutrient assimilations were obtained from the ratio C:N=9 as employed by Sundbäck et al (2000) and Alsterberg et al (2012) for microphytobenthos and from Redfield stoichiometric ratios (C:P=106 and C:Si=6.6). To calculate benthic regeneration contribution to microphytobenthos, theoretical nutrient demand was compared to benthic nutrient fluxes in dark conditions.…”
Section: Contribution Of Nutrient Regeneration To Benthic Primary Promentioning
confidence: 99%